Pengaruh Kepatuhan, Kecenderungan Negosiasi, Moral Pajak dan Manajemen Laba terhadap Voluntary Tax Compliance di Mediasi Persepsi Kebijakan Fiskal: (Study Kasus pada: UMKM Krupuk di Kenjeran) - Yuniati, Tri (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2024)
The purpose of this study was to analyze how the influence of taxpayer compliance, negotiation tendencies, tax morale and earnings management on valuntary tax compliance. and how the influence of taxpayer compliance, negotiation tendencies, tax morale and earnings management on valuntary tax compliance is mediated by fiscal policy. The study population is a taxpayer of Small and Medium Enterprises domiciled in in Kenjeran, East Java, the study sample involved 60 respondents using a purposive sampling method, the questionnaire as an instrument and processed using SEM Warp PLS 6.0 approach. The results showed that taxpayer compliance, the desire to negotiate, earnings management has a positive impact on valuntary tax compliance, but moral tax has a negative impact on valuntary tax compliance, taxpayer compliance, the desire to negotiate earnings management in fiscal policy mediation has a positive impact on valuntary tax compliance while tax morale in the mediation of fiscal policy has a negative impact on valuntary tax compliance. The novelty was found that taxpayers are obedient in carrying out their tax obligations influenced by the behavior of taxpayers, not because of regulations, behavior seen from economic, financial conditions by using a fiscal policy approach and conceptual approach based on a developing view of the tax policy.